2013
DOI: 10.4236/ojab.2013.21002
|View full text |Cite
|
Sign up to set email alerts
|

Urea Amperometric Biosensors Based on Nanostructured Polypyrrole and Poly Ortho-Phenylenediamine

Abstract: Urea Amperometric biosensor was obtained on the base of nanostructured polypyrrole (PPy) and poly orthophenylenediamine (POPDA). The optimal conditions for monomer electropolymerization were determined. The effect of supporting electrolyte and number of deposition cycles on the OPDA and Py electropolymerization were studied. It was proved that POPDA and PPy were affected by pH changes and responded to the ammonium, product of urease catalyzed reaction. SEM images of the modified Pt/PPy electrode were presented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…To do so, we used the developed electrodes, Pt/MPPy/GA-Urs or Pt/PPy/GA-Urs, as the working electrodes at fixed potential of +0.3 V vs. reference electrode (RE) for chronoamperometry [31]. Polymerization of the pyrrole was carried out with CV within the potential range of -1.0 to 1.0 V vs. RE at the scan rate of 100 mV s −1 [15]. The recorded current was directly related to the urea hydrolysis by urease.…”
Section: Electrochemical Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…To do so, we used the developed electrodes, Pt/MPPy/GA-Urs or Pt/PPy/GA-Urs, as the working electrodes at fixed potential of +0.3 V vs. reference electrode (RE) for chronoamperometry [31]. Polymerization of the pyrrole was carried out with CV within the potential range of -1.0 to 1.0 V vs. RE at the scan rate of 100 mV s −1 [15]. The recorded current was directly related to the urea hydrolysis by urease.…”
Section: Electrochemical Measurementmentioning
confidence: 99%
“…Immobilized urease on various supports as a biocatalyst converts urea to ammonium ( N H + 4 ) and bicarbonate ( HCO 3 ) ions. These ions change the electrical properties of the sample due to an increase in the pH of the solution according to the Nernst equation, which subsequently gives an electrical signal [2,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Entrapment of enzymes can occur during synthesis, which simplifies the biosensor preparation. Examples of biosensors based on conducting polymers include glucose biosensor based on GOx, 165–167 H 2 O 2 biosensor based on horseradish peroxidase, 165 urea biosensor based on urease, 168 and cholesterol biosensor based on cholesterol oxidase. 169 …”
Section: Use Of Organic Nanomaterials In Enzyme-based Biosensorsmentioning
confidence: 99%
“…Ivanova et al reported amperometric urea biosensor based on nanostructured polypyrrole. They found that the sensitivity of biosensors was increased with CNT and PPy [25]. In the previous studies done on biosensors based on CNT/PPy modified electrodes, the CNT was physically entrapped within the growing film by using some mediator which can alter the environment for the biomolecule to be immobilized.…”
Section: Introductionmentioning
confidence: 99%